Reliability of Urban Power Supply: Current Chal-lenges, Strategic Solutions, and Future Prospects - Anvar G. Saidkhujaev; Botir B. Kadraliev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: ensuring reliable power supply has become a critical requirement in modern energy systems due to increasing demand, the integration of renewable energy sources, and aging infrastructure. The transition from qualitative to quantitative, performance-based regulation—exemplified by standardized metrics such as SAIFI and SAIDI—represents a significant paradigm shift in the power sector. This approach promotes objective assessment of power system performance and creates strong incentives for utilities to improve service reliability, thereby reducing societal and economic risks associated with outages. Aim: to analyze the role and significance of standardized reliability metrics (SAIFI, SAIDI, etc.) in evaluating power system performance and to assess their impact on regulatory frameworks, utility investment strategies, and operational practices. Methods: review of international and national regulatory frameworks (IEEE, regional regulatory bodies); comparative analysis of the implementation of SAIFI/SAIDI metrics across various power systems; evaluation of statistical data on reliability performance and compliance with established targets; assessment of the influence of quantitative performance metrics on investment decisions, operational improvements, and strategic positioning of utilities. Results: demonstrated that standardized metrics such as SAIFI/SAIDI drive a shift from reactive to proactive reliability management; established that integration of these metrics into regulatory frameworks transforms reliability into a strategic business imperative; confirmed that quantitative performance-based regulation influences investment allocation, enhances operational practices, and improves the competitive positioning of utilities in the energy market.